2016
DOI: 10.4137/cmped.s40070
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine Growth Restriction: Antenatal and Postnatal Aspects

Abstract: Intrauterine growth restriction (IUGR), a condition that occurs due to various reasons, is an important cause of fetal and neonatal morbidity and mortality. It has been defined as a rate of fetal growth that is less than normal in light of the growth potential of that specific infant. Usually, IUGR and small for gestational age (SGA) are used interchangeably in literature, even though there exist minute differences between them. SGA has been defined as having birth weight less than two standard deviations belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
513
2
41

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 665 publications
(571 citation statements)
references
References 98 publications
15
513
2
41
Order By: Relevance
“…There was no surprise regarding management of SGA [16] and LGA [17] neonates: respondents' practices confirmed that inadequacy for gestational age raises concerns with regard to hypoglycemia. Likewise, preterm birth (<37 weeks GA) was concerning to all respondents as a driving factor of hypoglycemia.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…There was no surprise regarding management of SGA [16] and LGA [17] neonates: respondents' practices confirmed that inadequacy for gestational age raises concerns with regard to hypoglycemia. Likewise, preterm birth (<37 weeks GA) was concerning to all respondents as a driving factor of hypoglycemia.…”
Section: Discussionmentioning
confidence: 84%
“…Although neither group demonstrated a direct concern with hypertensive disease of pregnancy, studies have raised concerns regarding increasing body mass index in pregnant women [15], and it is becoming increasingly clear that obesity and diabetes go hand in hand [16]. It is also important to address the relationship between pregnancy-induced hypertension and disorders of fetal development, from intrauterine growth restriction (IUGR) [17,18] to neonates large for gestational age (LGA) [19] and even preterm birth [20,21] all of which facilitate the development of hypoglycemia. In their answers to the open-ended questionnaire items, the respondents also noted maternal medication use as an important factor, as many drugs (beta blockers, chlorpropamide, tocolytics, benzthiazide) can suppress the catecholamine response and prevent glycogenolysis, or stimulate the pancreatic beta cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased minute ventilation leads to a higher PaO2 (104-108 mmHg) and lower PaCO2 (27-32 mmHg) in the maternal circulation, resulting in a state of chronic respiratory alkalosis (pH 7.4-7.45) which is compensated for by an increase in renal excretion of bicarbonate (18-21 mmol/L). A simultaneous increase in oxygen consumption (20-40% above non-pregnant levels) occurs in order to fulfill the maternal, fetal and placental requirements [1][2][3].…”
Section: Journal Of Transmitted Diseases and Immunity Issn 2573 -0320mentioning
confidence: 99%
“…Intrauterine growth restriction is associated with an increased risk of perinatal morbidity and mortality compared with their appropriately grown counterparts, and much attention has been dedicated in recent years to prediction, early recognition, improved surveillance, as well as to timely planned delivery in order to minimize some of the adverse pregnancy outcomes [2].…”
Section: Introductionmentioning
confidence: 99%